PENGARUH METODE PEMBELAJARAN BLENDED LEARNING TERHADAP HASIL CAPAIAN PEMBELAJARAN MAHASISWA PROGRAM STUDI AKUNTANSI DAN MANAJEMEN PADA PERGURUAN TINGGI SWASTA DI BANJARMASIN - Ferra Maryana; Nova Abriano (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2017)
Abstract,This study aimed to give empirical evidences about the effect ofblended learning methods to learning outcomes of accounting andmanagement students in Banjarmasin and the difference learning outcomesof both student. The variables in this study were blended learning methodsand learning outcomes.The population in this study was the accounting and managementstudents in Banjarmasin. The data collected from the output of learningoutcomes of the respondents from true experiment. The samples techniqueused convenient sampling with 4 classes of accounting and management inSTIE Nasional Banjarmasin.The study gived empirical evidences that there were effect of blendedlearning methods to learning outcomes of accounting and managementstudents in Banjarmasin and the were not difference learning outcomes ofboth students.